Ottoman/Turkish visions of the nation, 1860-1950 - Gürpınar, Doğan (Palgrave Macmillan, 2013)
By examining the critical phase in the construction of a historical imagination from 1860 to 1950, this book demonstrates how history and historical imagery were instrumental in the Turkish nation-building process. Developing a thematic approach, it conveys the encounters with medieval Islam, medieval Europe, the Ottoman Empire, the Crusades and the French Revolution and shows how these historical themes were employed to serve national concerns. Gürpinar shows how these historical visions were posited to reinforce national visions in line with the modernist premises of the late Ottoman/Turkish national imaginations and identities. The study also demonstrates the continuities from the late Ottoman historical imaginations to the Kemalist/republican historical visions. It exposes the diverse agendas flourishing with the onset of the introduction of modern discourses and ideologies. The critical engagement with historiography reveals the transformations and continuities of Turkish nationalism from the late Ottoman Empire to the secular and radically modern republican Kemalist nationalism. This book is a contribution not only to the study of the development of modern Ottoman/Turkish historiography, but also to the origins of Turkish nationalism